1995
DOI: 10.1046/j.1525-1438.1995.05030170.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of the combination of serum markers, CA125, CASA and TPS in ovarian cancer

Abstract: The serum markers CA125, CASA and TPS were compared, with particular reference to the clinical applications of these tumor markers in the management of patients with ovarian cancer (discrimination of benign and malignant disease; indicating prognosis; predicting preclinical recurrence), (i) Using recommended cut-off points, CASA (>/=4 U ml-1 and TPS (>/=80 U l-1 showed similar sensitivities in ovarian carcinoma (56% and 57% respectively), though these were lower than with CA125 (85% >/= 35 U ml-1). The combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 6 publications
(6 reference statements)
0
16
0
Order By: Relevance
“…In an attempt to promote earlier diagnosis and improve monitoring of ovarian cancer, numerous markers have been studied (2)(3)(4)(5)(6). To date, none has been found suitable for widespread clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to promote earlier diagnosis and improve monitoring of ovarian cancer, numerous markers have been studied (2)(3)(4)(5)(6). To date, none has been found suitable for widespread clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…TPS is a serum tumor marker which has been studied in a wide variety of malignancies, such as lung, colon, breast, ovarian and urological cancers (Tarle et al, 1994;Devine et al, 1995;Kornek et al, 1995;van der Gaast et al, 1994;Klein et al, 1994).…”
Section: Cervical Cancermentioning
confidence: 99%
“…TPS is therefore believed to achieve higher specificity rates than TPA. TPS has been proposed as a useful tool in evaluating treatment response and early detection of relapse in a variety of human malignancies such as pancreatic, prostatic, cervical, ovarian cancer and gastrointestinal tumors (Banfi et al, 1993;Gitsch et al, 1992;Tarle et al, 1994;Devine et al, 1995;Kornek et al, 1995). Elevated TPS serum levels prior to therapy have been shown to parallel poor patient outcome in several malignancies, e.g., non-small cell lung cancer (van der Gaast et al, 1994).…”
mentioning
confidence: 99%
“…It also has been reported that CA125 is a better marker for nonmucinous ovarian malignancy compared with mucinous ovarian malignancy 1, 5. The management of patients with epithelial ovarian carcinoma, especially in establishing response to treatment or predicting clinical outcome, can be improved by combining the evaluation of CA125 levels with the evaluation other serum markers 2, 5, 8–10…”
mentioning
confidence: 99%
“…TPS can contribute to the prediction of prognosis and response to treatment in patients with different types of carcinoma 2, 5, 11. Compared with most other markers that measure tumor mass, the TPS level in serum reflects tumor cell activity 2, 5, 8, 9…”
mentioning
confidence: 99%